Character Education Management A Site Study At SMP Negeri 3 Salatiga - Sujanto, Sujanto (2012)
This study aims at describing (1) the characteristics of an integrated management of character education through learning at SMP Negeri 3 Salatiga, (2) the characteristics of an integrated management of character education through management at SMP Negeri 3 Salatiga, and (3) the characteristics of an integrated management of character education through students' development activity at SMP Negeri 3 Salatiga. This study used a qualitative method toward the management of character education, a site study at SMP Negeri 3 Salatiga. the method of data collection used observation, interview, and documentation study. The analysis used an interactive model of analysis of Miles and Huberman including data collection, data reduction, data display, and conclusion. The finding is about the character education management, a site study at SMP Negeri 3 Salatiga. The management of character education was done in three ways, an integrated character education through learning, management, and through students' development activity. 1) The integrated character education through learning included planning, implementation, and evaluation. Each of them tried to add the character values. 2) The integrated management through management includes planning of the programs, implementation of the programs and controlling of the programs. 3) The integrated character education through students' development activity included the activities done outside the learning hours to help the development of students based on the talent, potential, and need.